(untitled) (GESTIÓN Y TENDENCIAS, 2024)
This article questions purpose theory —which holds that individuals are motivated by subjective higher-order goals independent of social context— as an explanation of motivational phenomena and personality traits in the workplace. It proposes an interactionist perspective, which considers that higher-order goals result from the internalization of cultural meanings socialized in the context of social exchange, and that these influence the activation of personality traits and the motivational processes determining performance and organizational behavior. The theoretical and practical implications of this proposal are discussed: it accounts for behavioral variability as a function of situational characteristics and individual attributes, and offers an alternative to the essentialist and pathological interpretation of the personality traits associated with the dark triad or the Big Five.